Islam and Gender Equality: A Critical Exploration of Its Role in Global Peace - Aldi, Muhammad; Khairanis, Retisfa; Al Aziz, Sulthan (Yayasan Abdurrauf Cendekia Nusantara, 2025)
This research aims to analyze the Islamic perspective on gender equality and its role in supporting sustainable global peace. Within this framework, the research explores Islamic teachings that support gender justice and its contribution to social harmony and conflict resolution. This research approach uses a qualitative method with literature review as the main technique, utilizing classical and contemporary literature related to Qur'anic interpretation, hadith, and the views of Muslim scholars and scholars. The results show that Islam theologically encourages the principle of gender equality through the values of justice, respect, and cooperation between men and women. Gender equality practiced in Muslim societies has the potential to become the foundation for creating harmonious relationships, both within the family, community and between nations. The research also highlights that biased interpretations of religious texts often become obstacles in realizing this principle. The implications of this research provide an important contribution to efforts to create global peace through a religious value-based approach. The study encourages more inclusive cross-cultural and religious dialogue in addressing gender issues, while providing practical guidance for Muslim communities to reconstruct their understanding of Islamic teachings that support equality and peace. Abstrak: Penelitian ini bertujuan untuk menganalisis perspektif Islam mengenai kesetaraan gender dan perannya dalam mendukung perdamaian global yang berkelanjutan. Dalam kerangka ini, penelitian mengeksplorasi ajaran Islam yang mendukung keadilan gender serta kontribusinya terhadap harmoni sosial dan penyelesaian konflik. Pendekatan penelitian ini menggunakan metode kualitatif dengan kajian pustaka sebagai teknik utama, memanfaatkan literatur klasik dan kontemporer terkait tafsir Al-Qur’an, hadits, serta pandangan ulama dan cendekiawan Muslim. Hasil penelitian menunjukkan bahwa Islam secara teologis mendorong prinsip kesetaraan gender melalui nilai-nilai keadilan, penghormatan, dan kerja sama antara laki-laki dan perempuan. Kesetaraan gender yang dipraktikkan dalam masyarakat Muslim berpotensi menjadi fondasi untuk menciptakan hubungan yang harmonis, baik dalam lingkup keluarga, komunitas, maupun antarbangsa. Penelitian ini juga menyoroti bahwa interpretasi yang bias terhadap teks-teks agama sering kali menjadi hambatan dalam mewujudkan prinsip ini. Implikasi penelitian ini memberikan kontribusi penting dalam upaya menciptakan perdamaian global melalui pendekatan berbasis nilai agama. Kajian ini mendorong dialog lintas budaya dan agama yang lebih inklusif dalam mengatasi isu gender, sekaligus memberikan panduan praktis bagi komunitas Muslim untuk merekonstruksi pemahaman mereka terhadap ajaran Islam yang mendukung kesetaraan dan perdamaian. Kata kunci: Perspektif Islam, Kesetaraan Gender, Perdamaian Global